Pengaruh Edukasi tentang Bahaya Bullying dengan Metode Audiovisual terhadap Pengetahuan dan Sikap Remaja - Karimah, Nisa’ul; Andayani, Sri Astutik; Munir, Zainal (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
The purpose of this study was to analyze the effect of education on the dangers of bullying using audiovisual methods on adolescents’ knowledge and attitudes, considering that bullying is a serious psychosocial problem in schools which can cause long-term negative impacts such as trauma, decreased self-confidence, and reduced academic performance, and thus requires effective health education strategies to increase awareness and preventive attitudes. This study applied a Quasi-Experimental design with a pretest–posttest control group and involved 60 respondents selected through total sampling, divided into 30 adolescents in the intervention group and 30 in the control group. The intervention group received structured audiovisual-based education that presented material on the definition, types, impacts, and prevention strategies of bullying, while the control group did not receive any intervention. Data were collected using questionnaires on knowledge and attitudes and analyzed with the Wilcoxon test at a significance level of α = 0.05. The results showed that there was a significant increase in the knowledge and attitudes of the intervention group after receiving audiovisual education (Asymp. Sig = 0.000 < α = 0.05), whereas the control group did not experience significant changes due to the absence of intervention. These findings demonstrate that audiovisual education is more effective compared to conventional approaches because it combines visual and auditory stimulation, making learning materials easier to understand and remember, as well as more engaging for adolescents. In conclusion, audiovisual-based education is proven effective in improving adolescents’ knowledge and attitudes regarding the dangers of bullying, and its application should be considered as part of school-based health promotion programs, while future research can further explore its long-term effectiveness and the potential benefits of combining audiovisual methods with peer support and parental involvement in bullying prevention.